Urban Development in Western Siberia during 1930s - V. V. Aksarin; E. F. Sadykova (Научный диалог, 2023)
The subject of the study is the cities of Western Siberia, with a focus on socio-economic indicators such as education, demographics, population structure, healthcare, and housing conditions. This research introduces documents from the Russian State Archive of Economy into scholarly discourse for the first time. The influence of natural and geographical conditions on the development of Siberian cities was taken into account. Historical-comparative, historical-typological, and statistical research methods were used, as well as graphical representation of the data. A comparative quantitative analysis of the socio-economic indicators of Western Siberian cities revealed an increase in population with a majority of females over males, as well as a complexity of urban infrastructure due to the growth of medical, educational, scientific, and cultural institutions. The number of newly built residential buildings also increased, although their level of improvement remained low. The overall proportion of industrial enterprises in the cities increased, although the share of large enterprises was small, with only Omsk and Novosibirsk having slightly less than 50 % of them, and an average annual workforce exceeding 20,000 people. Examining the historical experience of development in Western Siberian cities contributes to a better understanding of the region’s settlement system history.